Overview of the evolution of agricultural mechanization in Nigeria - Takeshima, Hiroyuki; Lawal, Akeem (International Food Policy Research Institute, 2018)
Demand for mechanization in Nigeria is growing in a fairly consistent way predicted by economic theories. The farming system has intensified and the use of animal traction has grown at a substantial rate. Demand side factors considerably explain the low adoptions of tractors in Nigeria. Where demand is sufficient for tractors, the private sector has emerged over time as a more efficient provider of hiring services (particularly farmer-tofarmer services) than the public sector. Conditions are consistent with the hypotheses that, because of generally low support for the agricultural sector in Nigeria in the past few decades, agricultural mechanization (tractor use in particular) has remained low despite the declining share of the workforce engaged in the agricultural sector. Agricultural transformation in the form of a declining agricultural labor force has happened partly through the growth in the oil industry since the 1970s. Instead of inducing further exit from farming, tractor adoptions in Nigeria might have helped those who have remained in farming to start expanding their production scale. A knowledge gap, however, still remains regarding the dominance of large tractors and the potential effects of tractor adoptions on smallholders who have yet to adopt them.